PENERAPAN ARSITEKTUR EKOLOGI DALAM PERANCANGAN PUSAT PENELITIAN AGRIKULTUR DI KABUPATEN SRAGEN - Amna, Lailatul; Iswati, Tri Yuni; Singgih, Edi Pramono (Universitas Sebelas Maret Surakarta, 2017)
Indonesia is known as an agricultural country, which means Indonesia has high rate of agricultural production. However, Indonesia has not fully fulfilled its own food needs, seeing by the high number of food imports to Indonesia. Therefore, the government's agricultural development program is established which includes the development of science and technology (IPTEK) in agriculture. The application of Ecological Architecture theory is considered appropriate because it involves all related elements in the design of human, building and nature. This research is aimed to determine the design of research centre building which is able to facilitate the research activities in accordance with the standard of research space based on the principle of Ecological Architecture theory. The method used is data collection based on literature study, observation and comparation to the design object and application of Ecological Architecture theory, which is then applied as design strategies on the design object, starting from site selection, site analysis, as well as façade analysis. From the analysis that has been done then generated a research centre design that can support the sustainability of agricultural research activities based on the application of Ecological Architecture theory.